Contact dermatitis caused by prevention measures during the COVID-19 pandemic: a narrative review - Tang, Huimiao; Wang, Hao; Hamblin, Michael R.; Jiang, Lu; Zhou, Yanjun; Xu, Yidan; Wen, Xiang (Frontiers in Public Health, 2023)
During the outbreak of COVID-19, health care workers wore personal protective equipment including masks, gloves, and goggles for a long time. In order reduce the transmission routes of the virus, public places were sprayed with disinfectant. Moreover, the body, hands and clothing were frequently disinfected and washed for hygiene purposes. Studies have shown that these practices could easily destroy the skin barrier and irritate the skin. Long-term irritation or exposure to allergens may lead to the occurrence of contact dermatitis (CD). This article reviews reports of CD caused by various prevention and hygiene measures during the COVID-19 pandemic. The amount of skin damage caused by COVID-19 prevention measures could be decreased by improved education about skin management.